INCIDENCE AND PATHOGENICITY OF AEROMONAS SPP. IN RAW, PASTEURISED AND UHT MILK IN GREATER HYDERABAD MUNICIPAL CORPORATION, INDIA - Hareesh Didugu; T. Madhv Rao; N. Krishnaiah; VEnkateswara Reddy; Bhaskara Ramaraju Sagi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
125 samples (50 raw milk, 50 pasteurized milk and 25 UHT milk) were screened for Aeromonas spp. by both isolation and PCR assay. Conventional method had identified 32% in raw milk, 8% in pasteurised milk and none in UHT milk, whereas PCR assay detected 36% in raw milk, 10% in pasteurised milk and none in UHT milk suggesting that PCR was a better and sensitive method than the former method. Aerolysin (aer) was identified in 22.2%, 20% and no samples of raw milk, pasteurised milk and UHT milk, respectively. Thermostable cytotonic enterotoxin (ast) was observed in 33.3% samples of raw milk, 20% samples of pasteurised milk and none among UHT milk. Presence of Aeromonas spp. in pasteurised milk emphasizes the need for better hygiene to avoid post processing contamination. Presence of toxins of Aeromonas spp. is of major public health concern in case of food borne outbreaks.